Perumusan Indikator Kemiskinan dan Pengukuran Tingkat Kesejahteraan Masyarakat Desa Pagedangan Ilir, Kronjo, Tangerang - Widjaja, Achmad Reza (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
Apparatus often do not have standard and specific indicators for determining pre-prosperous families. It will, as a matter of fact, create an impact on targeting the beneficiaries of a welfare program, to the extent that it will cause the community welfare program less effective.This research aims to formulate indicators of poverty and measurement of community welfare in Pagedangan Ilir Village. The formulation of poverty indicators and measurements of welfare is a review from various poverty indicators or standard welfare measures, which are previuosly produced by government and other research institutions. In this research, a study by Center for International Forestry Research (CIFOR) becomes the basic benchmark to measure the community welfare in Pagedangan Ilir Village, by which the results obtained in the form of welfare based on indicator index, dimension index and aggregate index. The results show that in aggregate, there are no families in Pagedangan Ilir Village classified as "Very Poor", 32% of families are classified as "Poor", while 67% and 1% of them are classified as "Prosperous" and "Very Prosperous", respectively. In terms of classification of welfare levels according to the average aggregate welfare index, the family in Pagedangan Ilir Village is categorized as "Prosperous" with an index of 55.88.